(untitled) (Teología, 2015)
The present paper studies the Brief Divinum praeceptum (1915), a document used by Pope Benedict XV (1914-1922) for the institution of the Immaculate Conception School of Theology. This study has been conducted from the peculiar perspective of diplomatic, an auxiliary science of history, which focuses on establishing the authenticity of a text and the study of the origin of documents, their integrity and their proper interpretation. In the first place, this study shall specify both formal and material elements to be considered in order to analyze any document and the particular aspects of a type of a pontifical document generally referred to as “Papal Brief”. Then the reader will find a study and interpretation particularly focused on the “foundational Brief” showing its more salient peculiarities. The author also point out the “variable readings” identified when comparing an original to its early transcriptions, trying to trace possible “transcription families”. As extra information, there is a transcription of the original text including an explanation of acronyms as well as other worth mentioning peculiarities. Last, but not least, this study provides a translation into Spanish of the original text in Latin.